The Effect of Self-efficacy and Self-esteem Towards the Pt Garuda Food Indonesia Employee’s Job Satisfaction - Fadilah, M F; Siswanto, E; Nora, E; Juariyah, L; ., Syihabudhin (KnE Social Sciences, 2018)
work satisfaction is really significant in increasing employee’s retention. Work satisfaction is usually built and developed by the individual characters of the workers. This study aims to know the effect of self efficacy and self esteem towards employee’s work satisfaction. The population of this study is permanent employees in HCS division of PT. GarudaFood Putra Putri Jaya, Gresik, East Java. From 81 population, 53 samples are taken using simple random sampling technique. By using multiple linear regression analyzing technique, the result shows that self-efficacy and self-esteem positively and significantly affect the work satisfaction. Keywords: Self Efficacy, Self Esteem, Employee’s Work Satisfaction